PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS ANGGOTA DENGAN KEPUASAN ANGGOTA SEBAGAI VARIABEL INTERVENING (Studi Kasus Di Koperasi Simpan Pinjam Loh Jinawi) - Alifahrudin Irvan Yusuf, 13.05.51.0105 (Students Journal of Economic and Management, 2017)
The purpose of this study was to determine the effect of direct and indirect service quality, trust, corporate image, and customer satisfaction as an intervening variable on loyality. The population of this research is the member KSP Loh Jinawi.The total sample 100 respondents with method purposive sampling. Data obtained by the questionnaire. This research variable service quality (X1),trust (X2), corporate image (X3), customer satisfaction (Y1), and loyality (Y2). Data analysis with statistical analysis descriptive and path analysis. The result of the research indicated that the service quality (X1), trust (X2), coorporate image (X3) show that there are influance bigger than loyality(Y2) compared by intervening variable satisfaction (Y1).The result of lane analysis shows that service quality variable (X1) has direct effect on loyalty (Y2), trust (X2) has direct effect on loyalty (Y2), corporate image (X3) has direct effect on loyalty (Y2). The conclusion from the study of the quality service (X1), trust (X2), corporate image (X3) has direct effect on loyalty (Y2) compared through satisfaction (Y1) as intervening variable. It is suggested to KSP Loh Jinawi to improve service quality, in terms of tangible, reliability, responsiveness, assurance and emphaty. In the belief KSP Loh Jinawi should be able to increase the trust of its members and on corporate image should KSP Loh Jinawi able to show stability. Keywords : Quality of service, trust, corporate image, satisfaction and loyalty